Impact of Board and Audit Committee Characteristics on Adoption of Integrated Reporting of Listed Banks in Sri Lanka. - Anojan, V.; Ramesh, S. (University of Sri Jayewardenepura, 2021)
The main purpose of the study is to identify the impact of board and audit committee characteristics on the adoption of integrated reporting by listed banks in Sri Lanka. Content analysis investigates information related to the board and audit committee characteristics and integrated reporting. Research data were collected from all listed 12 banks’ five annual reports from 2016 to 2020. Descriptive, correlation, and regression analyses were performed with the help of STATA’s latest version. We found that listed banks did not adopt fully integrated reporting and the level of adoption has reduced in 2020 than 2019 in Sri Lanka. Listed-banks nearly adopted seven content elements out of eight content elements of integrated-reporting in Sri Lanka. Correlation analysis confirmed that gender diversity, independent directors, audit committee meetings, and audit committee independence have a significant relationship with the adoption of integrated-reporting. According to regression analysis, tested independent variables of the study have 34.33 per cent impact on the dependent variable in this study. Further, gender diversity, independent directors, and audit committee meetings have a significant impact on the adoption of integrated- reporting by listed-banks in Sri Lanka. Listed banks give more consideration on female representation and independence of the board, adequate audit committee meetings and independence of the audit committee to improve integrated-reporting and achieve its full adoption in the future. The government and other regulatory bodies should provide adequate knowledge and awareness to improve integrated- reporting adoption by listed-firms in Sri Lanka.
Keywords: Audit Committee; Board Characteristics; Integrated Reporting; Listed Banks